Dari Sejarah ke Studi Hadis: Memahami Metode Sejarah Kritis dan Penanggalan Hadis di Barat - Mohammad Nur Ahsan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
From History to Hadith Studies: Understanding Critical Historical Methods and Dating Hadith in the WestThis article describes the historical research method implemented by hadith scholars in the West. Since Ignaz Goldziher developed Aloys Sprenger’s idea, scholars of hadith in the West have always based their studies on critical historical methods to formulate various methods of dating hadith as a source of historical reconstruction in the early periods of Islamic development. The reality of hadith studies in the West based on research methodology in the historical discipline has not yet received the attention of Muslim scholars, not least in Indonesia, which provides a critical review of the results of studies in the West. Instead of proposing a critique from a compatible paradigm, the arguments put forward are often based on assumptions that originate in the tradition of traditional hadith criticism. This article examines literature sources using a qualitative method and a narrative approach. Starting from the description of the formation and development of historical science in Europe, this article shows how the historical method was used by scholars of Islamic studies in the West to formulate four types of methods of dating hadith. The application of one or more of these methods in the study of hadith involves considering its suitability with the sources' characteristics. However, Muslim scholars’ involvement in the discourse of hadith studies in the West undoubtedly departs from the paradigm, theory, and method of historical research